1972
DOI: 10.1017/s0021859600025892
|View full text |Cite
|
Sign up to set email alerts
|

A glutathione deficiency in the red cells of certain Merino sheep

Abstract: Red cell GSH concentrations were measured in 83 pure-bred and 65 cross-bred Tasmanian Merino sheep. A bimodal distribution was found; 40% of sheep had mean GSH values of 27-3 + 1-2 mg and 60 % had 92-2 ±1-5 mg/100 ml red cells. Family data are limited, but they suggest that this difference is under genetic control, the gene for low GSH levels being dominant to that for high. Unlike GSH-low type Finnish Landrace sheep, GSH-low type Merino sheep do not have lower than normal red cell sodium and potassium concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1973
1973
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 2 publications
(2 reference statements)
0
7
0
Order By: Relevance
“…Dick et al, (1969) suggested that sodiumpotassium activated ATPase activity is inhibited by oxidized glutathione. Tucker and Kilgour (1972) reported that sheep with genetically determined deficiency of reduced GSH in their red cells had lower than normal red cell potassium, and probably also lower red cell sodium concentrations. Skotnicka et al, (2010).…”
Section: Resultsmentioning
confidence: 99%
“…Dick et al, (1969) suggested that sodiumpotassium activated ATPase activity is inhibited by oxidized glutathione. Tucker and Kilgour (1972) reported that sheep with genetically determined deficiency of reduced GSH in their red cells had lower than normal red cell potassium, and probably also lower red cell sodium concentrations. Skotnicka et al, (2010).…”
Section: Resultsmentioning
confidence: 99%
“…Erythrocytes with GSH deficiency found in Churra sheep were characterized by the absence GSH deficiency in sheep of high amino acid levels and by a potassium concentration which did not significantly differ from that of normal cells. It seems then that GSH deficiency in Churra sheep does not follow the Finn type whereas it could be similar to the Merino type described by Tucker & Kilgour (1972).…”
Section: Abstract: Glutathione Erythrocytes Sheepmentioning
confidence: 87%
“…of animals The genetic control of GSH concentrations seems to be complex according to results obtained in different sheep breeds. A type of GSH deficiency was described in Tasmanian Merino sheep (Tucker & Kilgour 1972) associated with diminished y-glutamyl(:ysteine synthetase (GC-S) activity and caused by the dorninant gene GSHL. However, a similar type of biochemical GSH deficiency was indicated i n Australian Merino sheep (Board et nl.…”
Section: Abstract: Glutathione Erythrocytes Sheepmentioning
confidence: 99%
“…Tasmanian Merino sheep show a bimodal distribution in the concentration of reduced glutathione (GSH) in their red cells, 40% of sheep having GSH values of around 27 mg GSH/100 ml red cells and 60% with values of about 92 mg GSH/100 ml red cells (Tucker & Kilgour, 1972). The GSH deficiency was shown to be due to an impaired activity of y-glutamyl cysteine synthetase (y-GC-S), the enzyme catalysing the first step of GSH biosynthesis (Tucker, Kilgour & Young, 1976).…”
mentioning
confidence: 99%